Correlating surface adsorbate configuration and electrochemical performance of IrO 2 during seawater-relevant electrolysis - Tianyou Mou; Daniela A. Bushiri; Daniel V. Esposito; Jingguang G. Chen; Ping Liu (Proceedings of the National Academy of Sciences, 2026)
Seawater electrolysis alleviates freshwater demand to produce clean hydrogen while eliminating the need for water purification steps. The anodic process, seawater oxidation, typically requires high overpotentials and yields low selectivity to oxygen via the oxygen evolution reaction (OER), primarily due to the competing chlorine evolution reaction (CER) and hypochlorite evolution reaction (HCER) in pH-neutral conditions. Here, combining in situ surface-enhanced Raman characterization, grand canonical density functional theory-based calculations, and kinetic Monte Carlo simulations, we report the evolution of surface adsorbate configurations driven by applied potential and pH during seawater-relevant OER over IrO 2 , a highly OER-active and chloride-corrosion-resistant catalyst. As a result, the chemical properties of active sites, and thereby the kinetics of OER and CER/HCER, are effectively tuned. However, it is revealed that there is no optimal combination of potential and pH to achieve both high activity and high selectivity for seawater-relevant OER. To address this limitation, we establish a correlation between activity/selectivity and surface adsorbate configurations, enabling the optimization of highly active and OER-selective IrO 2 -based catalysts in seawater-relevant oxidation by modulating the local adsorbate environment of active sites.